Mucosal Microbiome Profiles Polygenic Irritable Bowel Syndrome in Mestizo Individuals - Arredondo-Hernández, Rene; Schmulson, Max; Orduña, Patricia; López-Leal, Gamaliel; Zarate, Angel-Mario; Alanis-Funes, Gerardo; Alcaraz, Luis David; Santiago-Cruz, Rubí; Cevallos, Miguel A.; Villa, Antonio R.; Ponce-de-León Rosales, Samuel; López-Vidal, Yolanda; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Irritable bowel syndrome (IBS) is the most frequent functional gastrointestinal disorder, worldwide, with a high prevalence among Mestizo Latin Americans. Because several inflammatory disorders appear to affect this population, a further understanding of host genomic background variants, in conjunction with colonic mucosa dysbiosis, is necessary to determine IBS physiopathology and the effects of environmental pressures. Using a simple polygenic model, host single nucleotide polymorphisms (SNPs) and the taxonomic compositions of microbiota were compared between IBS patients and healthy subjects. As proof of concept, five IBS-Rome III patients and five healthy controls (HCs) were systematically studied. The human and bacterial intestinal metagenome of each subject was taxonomically annotated and screened for previously annotated IBS, ulcerative colitis, and Crohn´s disease-associated SNPs or taxon abundance. Dietary data and fecal markers were collected and associated with the intestinal microbiome. However, more than 1,000 variants were found, and at least 76 SNPs differentiated IBS patients from HCs, as did associations with 4 phyla and 10 bacterial genera. In this study, we found elements supporting a polygenic background, with frequent variants, among the Mestizo population, and the colonic mucosal enrichment of Bacteroides, Alteromonas, Neisseria, Streptococcus, and Microbacterium, may serve as a hallmark for IBS